1994
DOI: 10.1152/ajpendo.1994.266.2.e211
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone treatment of obese women for 5 wk: effect on body composition and adipose tissue LPL activity

Abstract: Because it has been found that growth hormone (GH) treatment of GH-deficient adults is able to reduce the total fat mass, the present study was undertaken to investigate the effect of GH treatment in obese subjects. The investigation was a double-blind placebo-controlled crossover study in which nine obese females were treated with GH (0.03 mg.kg ideal body wt-1.day-1) and placebo for 5 wk. Body composition was determined by dual-energy X-ray absorptiometry, and the quantity of intra-abdominal adipose tissue w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
94
2
2

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(106 citation statements)
references
References 24 publications
8
94
2
2
Order By: Relevance
“…The findings reported here are not unprecedented, since improved glucose metabolism has been described in three of 24 clinical trials [5][6][7]. However, many studies report that growth hormone treatment of obesity has either little to no effect [8,9,11,12] or negative effects [31][32][33][34] on glucose metabolism. A recent metaanalysis comparing 24 studies in which growth hormone was used to treat obesity revealed a small increase in fasting plasma glucose and fasting insulin [35].…”
Section: Discussionsupporting
confidence: 47%
“…The findings reported here are not unprecedented, since improved glucose metabolism has been described in three of 24 clinical trials [5][6][7]. However, many studies report that growth hormone treatment of obesity has either little to no effect [8,9,11,12] or negative effects [31][32][33][34] on glucose metabolism. A recent metaanalysis comparing 24 studies in which growth hormone was used to treat obesity revealed a small increase in fasting plasma glucose and fasting insulin [35].…”
Section: Discussionsupporting
confidence: 47%
“…19 This is consistent with the failure of GH treatment to signi®cantly enhance diet-induced fat loss in obese patients observed in other studies 9,10,12 with the exception of a recent one 27 in which the patients received an energy intake (62.79 kJ/kg IBW daily) 50% higher than the one adopted in our protocol. A more striking decrease in body fat, especially at visceral level, 28 is well documented in obese patients receiving GH while on a normocaloric diet. 13,28,29 The observation of a smaller LBM loss in GHtreated women in spite of no signi®cant differences in changes of body weight and fat mass between the two groups may not be in contradiction; in fact, statistically insigni®cant but not negligible variations in parameters of body composition may account for the apparent discrepancy of these results.…”
Section: Discussionmentioning
confidence: 94%
“…A more striking decrease in body fat, especially at visceral level, 28 is well documented in obese patients receiving GH while on a normocaloric diet. 13,28,29 The observation of a smaller LBM loss in GHtreated women in spite of no signi®cant differences in changes of body weight and fat mass between the two groups may not be in contradiction; in fact, statistically insigni®cant but not negligible variations in parameters of body composition may account for the apparent discrepancy of these results. The good correspondence between body weight loss estimated by Growth hormone treatment in obesity M Tagliaferri et al DEXA (sum of fat mass and LBM losses) and body weight estimated using a balance gives consistency to the data.…”
Section: Discussionmentioning
confidence: 94%
“…In contrast, a signi®cant decrease in body fat, especially at visceral level, 135,136 is well documented in obese patients receiving GH, while on a normocaloric diet. 45,135 ± 137 This ®nding is in line with the reduction of body fat observed in ad libitum fed, but not in calorie-restricted, beef steers after bovine GH administration.…”
Section: Effects Of Gh Administration On Body Composition In Obesitymentioning
confidence: 99%
“…Thus in a number of studies, GH administration displayed bene®cial effects on body composition in obese patients either on weight-maintaining diets 135,137 or undergoing both moderate 76,126 and severe 131,132 caloric restriction. GH administration to obese patients appears to be a safe treatment, although a few adverse effects have been reported in some trials.…”
Section: Effects Of Gh Administration On Body Composition In Obesitymentioning
confidence: 99%